Los suenos proféticos del Palmerín de Olivia : a la luz de Los Commentarii in Somnium Scipionis de Macrobio - González, Javier Roberto (1998)
Fil: González, Javier Roberto. Pontificia Universidad Católica Argentina; Argentina